Redes sociales y usos educativos - Meza Castillo, Andrea Johanna (2015)
This paper describes the social networks, in particular, emphasizes the use of YouTube for educational purposes. In YouTube you can find educational, entertaining, musical information, etc. with audiovisual content with higher quality reception for their creative and explanatory clarity. One of the major benefits of YouTube is to provide a wide range of opportunities and alternatives for education where they can constantly interact at any time with different cultures. When news content tend to be abundant in creativity, teaching and imagination, usually they have greater acceptance and interest of young people and consequently a satisfactory feedback is created. The opposite occurs with monotonous information content present in the traditional way of teaching, which is associated with the memorization and repetition of a specific topic. The use of new Information Technology and Communication (ICT) is a major contribution in the field of teaching and learning. In this regard, YouTube takes into account the change of the written to the visual. The writing is no longer the only path to disseminate all kinds of information, there are other activities that work as mediators of learning: design, find, interact, create, etc.